Os direitos sociais clássicos e universais: o estado social e o estado democrático de direito - Simões, Carlos Jorge Martins (2012)
The democratic rule-of-law is a legal-political formation of a different nature of the welfare state. Its institution has not resulted from the reform of the rule-of-law and the welfare state, but its historical and logical-categorical synthesis. It presents unique distinctions and specifications, in which political density required the constitutionality of its own state formation. It originated pioneer universal social rights, integrated into civil and political rights, forming an indivisible interdependent and interrelated category. This follows from the insemination of Fundamental Principles and Guarantees, coupled with constitutional ethical values, which ends in new state institutions. As a result, it links the state onto social policies applied through plans, programs and projects. In an original way it separated the Economic and Financial Order from the Social Order, characterizing it not as a mere reflection of mechanistic economic development, but by a set of axiological guidelines disconnected from the market, to be enforced by state initiative with the participation of civil society. Social rights acquired thus a new legal-political nature, which requires not only the seizure of teleological criteria, generally reduced into social purposes like the minimum basic necessities, but by institutional criteria, based on assumptions of its acquisition, allowing the distinction into classic, linked to employment and universal which is related to incomes. Its universalization is consistent with the institution of participatory democracy, with new functional links and the reform of state policies. It thus promotes the overcoming of the traditional strict separation between state and civil society by direct democracy, particularly through councils as it assists in the establishment and control of social policies, as well as the federal decentralization of the judiciary branch in three dimensions; administrative, financial and functional and also new institutional competencies and charges for Federal and State Courts which are holders of the new and more effective constitutional rights